STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI SEKOLAH MENENGAH PERTAMA NEGERI 21 MUARO JAMBI - Doni Alparezi; Salahuddin Salahuddin; Mukhlis Mukhlis (Jurnal Manajemen Pendidikan, 2026)
This research is driven by teacher discipline challenges at SMP Negeri 21 Muaro Jambi, primarily caused by geographical constraints and difficult road access. This study aims to analyze the principal's strategies, identify the supporting and inhibiting factors, and evaluate the effectiveness of their implementation. A descriptive qualitative approach was employed, with data gathered through observation, in-depth interviews, and documentation. The data were then analyzed using qualitative descriptive techniques. The findings reveal that the principal's strategies involve exemplary leadership, motivational support, fostering teamwork, mandatory lesson plan (RPP) preparation, and the enforcement of a reward and punishment system, including fines for tardiness. Key supporting factors include decisive leadership and a harmonious work environment, whereas poor road infrastructure remains the primary obstacle. In conclusion, these strategies effectively enhance teachers' disciplinary commitment. The study suggests integrating digital attendance systems to optimize performance evaluation.